The NS1 protein of contemporary West African Zika virus potentiates viral replication and reduces innate immune activation - Machmouchi, Dana; Courageot, Marie-Pierre; Ogire, Eva; Redecke, Lars; Kohl, Alain; Desprès, Philippe; Roche, Marjolaine (PLoS neglected tropical diseases, 2024)
Mosquito-borne Zika virus (ZIKV) from sub-Saharan Africa has recently gained attention due to its epidemic potential and its capacity to be highly teratogenic. To improve our knowledge on currently circulating strains of African ZIKV, we conducted protein sequence alignment and identified contemporary West Africa NS1 (NS1 CWA ) protein as a highly conserved viral protein. Comparison of NS1 CWA with the NS1 of the historical African ZIKV strain MR766 (NS1 MR766 ), revealed seven amino acid substitutions. The effects of NS1 mutations on protein expression, virus replication, and innate immune activation were assessed in human cells using recombinant NS1 proteins and a chimeric viral clone MR766 with NS1 CWA replacing NS1 MR766 . Our data indicated higher secretion efficiency of NS1 CWA compared to NS1 MR766 associated with a change in subcellular distribution. A chimeric MR766 virus with NS1 CWA instead of authentic protein displayed a greater viral replication efficiency, leading to more pronounced cell death compared to parental virus. Enhanced viral growth was associated with reduced activation of innate immunity. Our data raise questions of the importance of NS1 protein in the pathogenicity of contemporary ZIKV from sub-Saharan Africa and point to differences within viral strains of African lineage.